Pengaruh Penerangan terhadap Stres dan Produktivitas Karyawan PT. X Purworejo - Satwika Ganendra; IJK Sito Meiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2018)
The purpose of this study was to determine the effect of illumination on stress and productivity. The research subjects were 60 employees of Purworejo X Plant located in the final part of final eyelash cutting. Stages of data analysis in this study, by studying data productivity level and employee stress before and after the treatment using statistical techniques T. Test. The results showed that the change in lighting intensity of Kepmenkes standard numb. 1405 in 2002 amounted to 1000 lux to 2000 lux according to the standard of Illuminating Engineering Society based on experiments that have been done to increase employee productivity as much as 22% (pre: M: 74.39, SD: 4.35, post: M: 105.48, SD: 9.77) and reduce stress levels from employees as much as 11% (pre: M: 3.8367, SD: 0.171, post: M: 2.9313, SD: 0.18001). The conclusion of this experiment is an increase in lighting level of 1000 lux in accordance with the work of more detail can increase work productivity and reduce employee stress levels.